Novel lignin nanoparticles for oral drug delivery. Issue 28 (27th June 2019) - Alqahtani, Mohammed S.; Alqahtani, Ali; Al-Thabit, Abdullah; Roni, Monzurul; Syed, Rabbani
Abstract : Lignin nanoparticles (LNPs) were prepared with the objective of evaluating their application as a novel oral drug delivery system. Abstract : Lignin nanoparticles (LNPs) were prepared with the objective of evaluating their application as a novel oral drug delivery system. Curcumin, a polyphenolic natural compound, was used as a lipophilic drug model, as its poor solubility and low oral bioavailability limit its therapeutic efficacy. Optimized nanoparticles were prepared using phase separation and stabilized by citric acid crosslinking. Physicochemical properties of the prepared curcumin-loaded nanoparticles, including particle size, size distribution, morphology, and encapsulation efficiency were characterized. The average particle diameter of curcumin-loaded LNPs was 104 nm, whereas the encapsulation efficiency of curcumin in the nanoparticles was 92%. Stability analyses of curcumin-loaded nanoparticles demonstrated enhanced protection of the entrapped curcumin under storage conditions. Furthermore, in vitro release assays revealed that curcumin-loaded LNPs have high stability in simulated gastric fluid and slow release under intestinal conditions as desirable. To evaluate absorption and bioavailability, we also investigated cellular uptake and transepithelial permeability of curcumin-loaded LNPs using Caco-2 cell monolayers. Cell viability studies revealed that curcumin-loaded LNPs did not induce toxicity in Caco-2 cells. The nanoparticle formulation enhanced curcumin cellular uptake and intestinal permeation compared to free curcumin. Incubation of LNPs on a Caco-2 cell monolayer led to a fivefold increase in apparent permeability compared to free curcumin. Furthermore, in vivo pharmacokinetics experiments showed that the LNP system increased the bioavailability of curcumin by ten-fold compared with the administration of unformulated curcumin. Overall, our findings indicate that the novel LNPs have great potential to be applied as an effective oral drug delivery system, especially for drug molecules with low solubility and limited bioavailability.